Munson's fluid mechanics - Gerhart, Philip M.; Gerhart, Andrew L.; Hochstein, John I.; Munson, Bruce Roy (John Wiley & Sons, 2017)
This edition offers comprehensive topical coverage, with varied examples and problems, application of visual component of fluid mechanics, and strong focus on effective learning. The text enables the gradual development of confidence in problem solving.